Effects of Exercise Training on Heart Rate Variability in Chagas Heart Disease - Nascimento,Bruno Ramos (2014)
Background: Heart rate variability (HRV) is a marker of autonomic dysfunction severity. The effects of physical training on HRV indexes in Chagas heart disease (CHD) are not well established. Objective: To evaluate the changes in HRV indexes in response to physical training in CHD. Methods: Patients with CHD and left ventricular (LV) dysfunction, physically inactive, were randomized either to the intervention (IG, N = 18) or control group (CG, N = 19). The IG participated in a 12-week exercise program consisting of 3 sessions/week. Results: Mean age was 49.5 ± 8 years, 59% males, mean LVEF was 36.3 ± 7.8%. Baseline HRV indexes were similar between groups. From baseline to follow-up, total power (TP): 1653 (IQ 625 - 3418) to 2794 (1617 - 4452) ms, p = 0.02) and very low frequency power: 586 (290 - 1565) to 815 (610 - 1425) ms, p = 0.047) increased in the IG, but not in the CG. The delta (post - pre) HRV indexes were similar: SDNN 11.5 ± 30.0 vs. 3.7 ± 25.1 ms. p = 0.10; rMSSD 2 (6 - 17) vs. 1 (21 - 9) ms. p = 0.43; TP 943 (731 - 3130) vs. 1780 (921 - 2743) Hz. p = 0.46; low frequency power (LFP) 1.0 (150 - 197) vs. 60 (111 - 146) Hz. p = 0.85; except for high frequency power, which tended to increase in the IG: 42 (133 - 92) vs. 79 (61 - 328) Hz. p = 0.08). Conclusion: In the studied population, the variation of HRV indexes was similar between the active and inactive groups. Clinical improvement with physical activity seems to be independent from autonomic dysfunction markers in CHD.